PERHITUNGAN HARGA JUAL MASSA COR CN-17A SEBAGAI DASAR USULAN TARIF BAHAN BAKU KERAMIK PADA BTIKK - I Nyoman Normal; Arifin Siagian (Forum Manajemen STIMI Handayani Denpasar, 2021)
The aims of this research are: (1) calculating and evaluating the basic tariff for the latest raw material technology services on the bulk selling price of CN-17A castings; (2) determine the effect of raw material technology service rates on the cost of production; (3) determine the effect of raw material technology service rates on profitability; and (4) proposing tariffs for new raw material technology services. The results showed that: (1) The theoretical raw material technology service tariff for CN-17A pouring mass was IDR 8,648.60 per liter, but the last tariff was IDR 4,500 per kg; (2) The tariff for raw material technology services affects the cost of goods manufactured. Raw material technology service rates are in accordance with PP. 51 of 2018 resulted in the cost of production of Rp 4,090.91 per kg, while the cost of goods manufactured should be Rp 8,862.36 per liter; (3) Tariffs for raw material technology affect profitability. The tariff for raw material technology services according to PP. 51 of 2018 is lower than it should be IDR 75.80 per kg (liter); and (4) the latest tariffs for ceramic raw material technology services need to be revised to reflect more realistic conditions.